Serious games in Science and Mathematics Education: a scoping umbrella review - Ayaz Karimov; Mirka Saarela; Tommi Kärkkäinen (Serious Games Society, 2024)
Many studies focused on reviewing the use of serious games as part of Science and Mathematics Education. While previous reviews focused on various educational levels and subjects, narrowing the scope to Science and Mathematics Education provides more targeted insights that can inform instructional strategies and curriculum development. In this article, we summarize 16 systematic reviews and meta-analyses with a total of 535 primary studies investigating the impact of serious games in Science and Mathematics Education. Our findings highlight that serious games can motivate and engage students while improving their learning outcomes and leading to improved cognitive skills. However, negative reports on the use of serious games in Science and Mathematics Education such as demotivation, anxiety, and limited effects on learning were also observed. Overall, this paper contributes to human-computer interaction (HCI) by providing a comprehensive analysis of serious games' impact on students' moods and learning outcomes in Science and Mathematics Education, highlighting the role of teachers and proposing future research directions for game-based learning.